Pramipexole Extended Release: A Novel Treatment Option in Parkinson's Disease - Wolfram Eisenreich; Bernd Sommer; Sebastian Hartter; Wolfgang H. Jost (Parkinson's Disease)
Pramipexole, the most commonly prescribed dopamine agonist worldwide, meanwhile serves as a reference substance for evaluation of new drugs. Based on numerous clinical data and vast experiences, efficacy and safety profiles of this non-ergoline dopamine agonist are well characterized. Since October 2009, an extended-release formulation of pramipexole has been available for symptomatic treatment of Parkinson's disease. Pramipexole administration can be cut down from three times to once a day due to the newly developed extended-release formulation. This is considerable progress in regard to minimizing pill burden and enhancing compliance. Moreover, the 24 h continuous drug release of the once-daily extended-release formulation results in fewer fluctuations in plasma concentrations over time compared to immediate-release pramipexole, given three times daily. The present study summarizes pharmacokinetics and all essential pharmacological and clinical characteristics of the extended-release formulation. In addition, it provides all study data, available so far, with regard to transition and de-novo administration of extended-release formulation for patients with Parkinson's disease. It further compares efficacy and safety data of immediate-release pramipexole with the extended-release formulation of pramipexole.